Analisis In Silico Metabolit Sekunder Lansium domesticum sebagai Agen Antimalaria Potensial yang Menargetkan Enzim Laktat Dehidrogenase (PfLDH) pada Plasmodium falciparum - Hanum, Laila; Nirwana, Rahma Julia; Oktariansyah, Yadi; Harvianti, Yuniar (Biogenesis: Jurnal Ilmiah Biologi, 2026)
Malaria continues to be a significant global infectious illness, with Plasmodium falciparum primarily responsible for the most severe and lethal cases, including cerebral malaria. P. falciparum lactate dehydrogenase (PfLDH), an essential enzyme in the parasite's glycolytic cycle, is a viable molecular target for the development of antimalarial drugs. The deficiencies in existing therapeutics underscore the necessity for novel candidate alternative drugs. Lansium domesticum, a native Indonesian plant, possesses bioactive compounds with potential antimalarial effects. This work sought to assess L. domesticum secondary metabolites as potential antimalarial agents using an in silico methodology. A total of 47 compounds were evaluated to forecast antimalarial efficacy, thereafter, assessing their physicochemical attributes, pharmacokinetic features, and toxicity profiles. Molecular docking was used to examine the interactions between potential drugs and the PfLDH target enzyme. Four compounds—is-3-Hexen-1-ol, Aromadendrene, Isoledene, and Hexadecanoic acid—fulfilled the necessary physicochemical, pharmacokinetic, and toxicological standards. Hexadecanoic acid demonstrated the most robust interaction with PfLDH, establishing three critical amino acid connections at the active site (GLY29, THR97, and HIS195) and exhibiting a superior binding affinity compared to control and natural ligands. The data indicate that hexadecanoic acid is a promising antimalarial candidate sourced from L. domesticum. Additional molecular dynamics simulations, together with in vitro and in vivo investigations, are required to validate its therapeutic efficacy.